2022
DOI: 10.3389/fphar.2022.921414
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Regulates Platelet Activation and Thrombosis via Caspase-3/GSDME Pathway

Abstract: Platelets play a central role in hemostasis and thrombosis, regulating the occurrence and development of thrombotic diseases, including ischemic stroke. Programmed death ligand 1 (PD-L1) has recently been detected in platelet, while the function of PD-L1 in platelets remain elusive. Our data reveal a novel mechanism for the role of PD-L1 on platelet activation and arterial thrombosis. PD-L1 knockout does not affect platelet morphology, count, and mean volume under homeostasis and without risk of bleeding, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, PD-L1-expressing platelets may partially explain the efficacy of ICIs even in PD-L1-negative tumors ( 169 ). Additionally, PD-L1 was found to activate platelets and amplify thrombosis ( 170 ).…”
Section: The Coagulome Reprograms the Tumor Microenvironment Towards ...mentioning
confidence: 99%
“…Interestingly, PD-L1-expressing platelets may partially explain the efficacy of ICIs even in PD-L1-negative tumors ( 169 ). Additionally, PD-L1 was found to activate platelets and amplify thrombosis ( 170 ).…”
Section: The Coagulome Reprograms the Tumor Microenvironment Towards ...mentioning
confidence: 99%
“…The cancer cells can activate the coagulation cascade and other prothrombotic processes in the host cell in absence of other predisposing factors for thrombosis. activation and arterial thrombosis [4], but several studies did not found a relationship between the presence of PD-L1 mutation and venous thrombosis [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 affected platelet αIIbβ3 outside-in signal transduction, an essential process for hemostasis and thrombosis, which might be mediated by IL-1β, as significantly reduced IL-1β release was found in NLRP3-deficient platelets ( 96 ). Furthermore, in thrombin activated-platelets, the caspase-3/GSDME pathway was upregulated, further regulating platelet integrin αIIbβ3 activation ( 97 ).…”
Section: Pyroptosis-induced Hemostasis Activation In Sepsismentioning
confidence: 99%